The shark flap: a modified internal mammary artery perforator flap for composite defects in head and neck reconstruction. Issue 1 (31st December 2023) - Scarabosio, Anna; Tel, Alessandro; Contessi Negrini, Filippo; Albanese, Roberta; Robiony, Massimo; Parodi, Piercamillo
Abstract: This report describes a multi-vector variant of IMAP flap which allows to reconstruct composite head and neck defects. It was named the 'shark flap' because of its shape: a main body (the regular IMAP) and a superior 'fin' based on a randomic vascular pathway.